Pengaruh Metode Copy The Master terhadap Keterampilan Membaca Puisi Siswa Kelas VII MTs PAB 2 Sampali - Amnur Rifai Dewirsyah (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This research was conducted to find out how "The Effect of Copy The Master's Method on Poetry Reading Skills of Class VII MTs PAB 2 Students". The location of this research was carried out at MTs PAB 2 Sampali Jalan. Black Market No. 69 Sampali Kec. Percut Sei Tuan. The population of this study were all classes VII-1 and VII-4 which amounted to 140 people. The experimental class or class that uses the Copy The Master method is class VII-1 with 35 students, while the control class or class without using the Copy The Master method is class VII-2 with 35 students. The method used in this research is the experimental method. In this research, a test instrument is used in the form of a poetry reading practice test. After calculating and processing the data carried out in the experimental class, the highest score was 11 people with a score of 70-84 and the lowest score was 10 people with a score of 70 and an average of 75.30 (good). While in the control class, the highest score was 1 student with a score of 70-84 and the lowest score was 1 student with a value of 0-49 and an average of 57.13 (enough). From the above results, we get tcount > ttable (6.98 > 1.71). Thus Ha is accepted. So in other words, the effect of the Copy The Master method on the poetry reading skills of class VII MTs PAB 2 Sampali students.